Institutional Weakness and Anti-Crime Experience in Mexico - Aguirre-Ochoa, Jerjes; Gómez, Mario (FLACSO - Sede Ecuador, 2021)
This paper discusses the relation between the political situation in Mexico and the evolution of organized crime through an analysis of the case of the state of Michoacan. It proposes that the failure of the policies implemented to combat crime in the country can largely be explained by the adoption of a police-military strategy that does not address the structural causes of violence. In terms of methodology, research was conducted from an ethnographic perspective based on a detailed examination of the anti-crime policies of recent Mexican presidential administrations and their impact on Michoacán; an analysis framed in the perspective of historical institutionalism. The study concludes that by taking advantage of the weakness of the state and broad gaps in its authority, power groups such as organized crime have successfully embedded themselves in the wider society and the specific, concrete dynamics of the Mexican political system, especially at the level of local governments, making the problem of criminality a political matter, not one that concerns only the police or the military.